Art Appreciation and the Method of Aesthetic Transfer - Zupančič Tomaž; Duh Matjaž (University of Maribor Press, 2013)
The method of aesthetic transfer is a modern teaching method in art education. It emphasizes the pedagogic value of the aesthetic experience. It is a comprehensive method, as it encompasses different parameters of art didactics. It affects lesson time allocation and determines content, methods, and teaching modes. It also affects motivation and final evaluation. The essence of the method of aesthetic transfer lies in transferring aesthetic messages from the artwork to students. The foundation and condition for a successful implementation of the method of aesthetic transfer is a high-quality art appreciation. There are several ways and methods for successfully developing art appreciation, the common objective of all being to allow students to see, perceive, and enjoy a work of art. Thus they enrich their artistic and aesthetic development, and establish a positive attitude towards art, while this method at the same time encourages their own artistic exploration.